Diagnostic Importance of Female External Genital Structure of Phlebotomine Sand Flies (Diptera:Psychodidae) as Observed by Scanning Electron Microscopy - J Mukhopadhyay; KN Ghosh (Memorias do Instituto Oswaldo Cruz, 1997)
Morphological description of sand flies has remained a neglected area. The different organs used in taxonomy have not yet been described adequately with the scanning electron microscopy (SEM). We have examined the external genital structures of females of three Old World phlebotomine sand flies under SEM and recorded the morphological variations of the organs. We have found the female external genital structures of the three species varied considerably in morphology. The importance of the female external genital structures in sand fly identification is indicated